Effectiveness of Mifepristone in the Treatment of Uterine Leiomyomata - Sinha, Mayurika; Kyal, A; Mukhopadhay, P (Nepal Journal of Obstetrics and Gynaecology, 2013)
Aims: The goal of this study was to determine the effects of mifepristone in perimenopausal women with leiomyomas, thereby to see a decrease in severity of symptoms and a decrease in size of the leiomyomas. Methods: This was a prospective study conducted at Eden HospitalMedical College and Hospital, Kolkatafrom July 2010 to June 2011. Fifty patients received 20-25mg mifepristone daily and comparison was made between pre and post treatment symptoms and leiomyoma volume. Results: All patients became amenorrhoeic after treatment, relieving heavy menstrual flow most complained of. Lower abdominal pain improved by > 80% in most patients and volume of leiomyoma decreased appreciably. The drug did not have any major side effects. Endometrial hyperplasia detected by ultrasound in 42% patients was only of simple type on biopsy. Conclusions: Mifepristone can be useful in treating symptomatic women with uterine leiomyoma in perimenopausal age group, in those awaiting surgery to stop bleeding and improve anaemia and to reduce size of tumor to make surgery technically easier, making it a cheaper alternative to GnRH agonists and without any major side effects. Nepal Journal of Obstetrics and Gynaecology / Vol 8 / No. 1 / Issue 15 / Jan- June, 2013 / 22-25 DOI: http://dx.doi.org/10.3126/njog.v8i1.8856